How the SDGs are implemented in China——A comparative study based on the perspective of policy instruments. (1st April 2021) - Xie, Hualin; Wen, Jiaming; Choi, Yongrok
Abstract: China is an important participant in and practitioner of the UN 2030 Sustainable Development Goals (SDGs). By quantitatively comparing policy instruments for implementing sustainable development goals of China, Japan and South Korea at the macro level, it is possible to analyze the lack and conflicts of China's policy instruments for achieving the Sustainable Development Goals, and to identify policy preferences and priorities for sustainable development. This article uses the content analysis method to build an analytical framework based on policy instruments and the social-economic-ecological dimensions of sustainable development. Through coding statistics, this research analyzes China's National Plan on Implementation of the 2030 Agenda for Sustainable Development (NPIASD), the Third National Basic Plan for Sustainable Development 2016–2035 (NBPSD) of South Korea, SDGs Implementation Guiding Principles (SIGP) of Japan. It was found that the current policy arrangements intervene in all aspects of sustainable development and provide various regulations and incentives to achieve SDGs. Compared with South Korea and Japan, symbolic and advisory instruments need to be strengthened in China. South Korea attaches great importance to ecological sustainability, social sustainability dimensions have the most policy instruments in China and Japan. While China's ecological sustainability dimensions have less proportion of policy instruments than Japan and Korea, a situation that needs adjustment and optimization. In the follow-up policy design and improvement of sustainable development, China should optimize the application structure of policy instruments and allocate policies in different dimensions of sustainable development rationally to give full play to the role and functions of policies.